2013
DOI: 10.1186/1476-069x-12-102
|View full text |Cite
|
Sign up to set email alerts
|

Maternal fish and shellfish consumption and wheeze, eczema and food allergy at age two: a prospective cohort study in Brittany, France

Abstract: BackgroundEnvironmental exposures, including dietary contaminants, may influence the developing immune system. This study assesses the association between maternal pre-parturition consumption of seafood and wheeze, eczema, and food allergy in preschool children. Fish and shellfish were studied separately as they differ according to their levels of omega-3 polyunsaturated fatty acids (which have anti-allergic properties) and their levels of contaminants.MethodsThe PELAGIE cohort included 3421 women recruited at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 37 publications
2
17
1
2
Order By: Relevance
“…In total, 866 records were excluded for duplicates, and 4,133 records were excluded after screening the titles and abstracts. The remaining 29 full‐text articles were assessed for eligibility, four of which were further excluded because of fish intake before pregnancy , retrospective cohort studies , and nested case–control studies . Finally, one RCT and 17 publications from 13 unique prospective cohort studies were included for maternal fish intake during pregnancy, and eight publications from five unique prospective cohort studies for fish intake in infancy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 866 records were excluded for duplicates, and 4,133 records were excluded after screening the titles and abstracts. The remaining 29 full‐text articles were assessed for eligibility, four of which were further excluded because of fish intake before pregnancy , retrospective cohort studies , and nested case–control studies . Finally, one RCT and 17 publications from 13 unique prospective cohort studies were included for maternal fish intake during pregnancy, and eight publications from five unique prospective cohort studies for fish intake in infancy.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this limited effect of n‐3 LC‐PUFAs may not persist as other components in fish come into play. Contaminants in fish, such as PCBs, PFCs, methylmercury, and lead, could probably counterbalance in part the effect of n‐3 LC‐PUFAs or even increase the risk of allergy .…”
Section: Discussionmentioning
confidence: 99%
“…However some notable examples are possible attenuation of a link between high maternal fish consumption and reduced eczema risk [92]; alongside a potentially stronger association between high fish intake and decreased risk of asthma [93]. Two subsequent studies have reported links between maternal shellfish intake and increased risk of eczema [92], and also food allergy in children [94].…”
Section: Areas For Future Researchmentioning
confidence: 99%
“…No link has been observed between fish intake during pregnancy and wheeze and/or asthma in childhood in most studies, nor in a meta-analysis [ 74 , 77 , 92 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. However, fish oil supplementation during pregnancy has been shown to decrease wheeze or asthma in childhood [ 130 , 131 , 132 ].…”
Section: Diet and Risk Of Asthmamentioning
confidence: 99%